Metode Rule Identification Urgency Solution (RIUS) dalam Penyusunan Naskah Akademik Peraturan Daerah - I Nyoman Prabu Buana Rumiartha; Ni Luh Gede Astariyani; Ni Kadek Ari Sukma Wedayanti; Kadek Angelina Yasana Putri (Jurnal Ilmiah Kebijakan Hukum, 2023)
The purpose of this research was conducted to offer a new method in the preparation of academic texts on laws and regulations. Academic Manuscripts contain the results of research regarding the contents of the content or proposals submitted to be regulated in a provision of statutory regulations and or regional regulations. Provisions related to the preparation of academic manuscripts have been regulated in laws and regulations, but a special method is needed in preparing academic manuscripts so that they are in accordance with the needs of the community. In this study using normative legal research methods. The findings in this study are that there is a novelty method that can be used in the preparation of academic manuscripts, namely the Rule Identification Urgency Solution (RIUS). With the RIUS method, an academic text can be used as a basis or basis for argumentation in the formation of laws and regulations or regional regulations. In conclusion, the RIUS method is a method that can analyze the rule of law, identify problems, the urgency of why these regulations are needed, and the solutions that can be provided. The RIUS method was first applied by researchers in preparing academic texts for regional regulations in the Badung Regency Government and Jembrana Regency Government, in this case researchers as experts in preparing academic manuscripts. Suggestions that can be given are that in the preparation of academic papers it is best to focus on analyzing what problems occur in society so that a regulation is needed.